An Overview of Triphala Guggulu and its Ingredients (AYUSHDHARA, 2023)
Triphala Guggulu, a polyherbal Ayurvedic formulation, is among the most significant and frequently used Guggulu Kalpana. Numerous references for preparing this formulation have been mentioned in various classical texts. It has been discussed under ‘Vranashotha’ and ‘Vidradhi’ rogadhikar in Chakradutt and Yogratnakar respectively. ‘Triphala Guggulu’ presnted in this article is mentioned in the Sharangdhara Samhita under ‘Vati Kalpana’. As the name itself suggests, this preparation contains Triphala and Guggulu as the main ingredient along with Pippali. It contains Guggulu in greater proportion than the other ingredients, much like any other Guggulu Kalpas. Triphala Guggulu is frequently used in the treatment of Shotha, Arsha, Bhagandara, Gulma, Vrana, and other ailments. It can also be used as a hypolipidemic drug on its own or in conjunction with other formulations. Several studies and experiments have also demonstrated its efficacy in atherosclerosis, coronary and arterial plaque, and elevated cholesterol levels in the blood. Thus, this article takes the approach of reviewing the experimental research work done on Triphala Guggulu as well as covers the pharmacological action of its ingredients.